2017
DOI: 10.1016/j.rse.2017.05.004
|View full text |Cite
|
Sign up to set email alerts
|

Inverting surface soil moisture information from satellite altimetry over arid and semi-arid regions

Abstract: Monitoring surface soil moisture (SSM) variability is essential for understanding hydrological processes, vegetation growth, and interactions between land and atmosphere. Due to sparse distribution of in-situ soil moisture networks, over the last two decades, several active and passive radar satellite missions have been launched to provide information that can be used to estimate surface conditions and subsequently soil moisture content of the upper few cm soil layers. Some recent studies reported the potentia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 37 publications
1
18
0
Order By: Relevance
“…Following the study conducted in Australia by the authors of [20], who demonstrated the effects of soil moisture and soil roughness on the nadir C-and Ku-band backscattering coefficients, recent studies demonstrated the capabilities of spaceborne altimeters for estimating SSM in semi-arid regions such as in west-Africa [21][22][23][24] and in Australia [25]. Indeed, thanks to their nadir-looking capability, altimeters minimize the attenuation by the vegetation layer and a relationship can be directly found with the moisture content of the underlying soil.…”
Section: Introductionmentioning
confidence: 98%
“…Following the study conducted in Australia by the authors of [20], who demonstrated the effects of soil moisture and soil roughness on the nadir C-and Ku-band backscattering coefficients, recent studies demonstrated the capabilities of spaceborne altimeters for estimating SSM in semi-arid regions such as in west-Africa [21][22][23][24] and in Australia [25]. Indeed, thanks to their nadir-looking capability, altimeters minimize the attenuation by the vegetation layer and a relationship can be directly found with the moisture content of the underlying soil.…”
Section: Introductionmentioning
confidence: 98%
“…A number of literature have studied Lake Victoria using various satellite remotely sensed products, e.g., satellite radar altimetry to observe the lake's water level variations (e.g., Awange et al, 2013b;Uebbing et al, 2015;Sichangi and Makokha, 2017) and their importance for flood monitoring (Birkett et al, 1999), the Gravity Recovery and Climate Experiment (GRACE) for studying the lake's total water storage (TWS) changes (e.g., Awange et al, 2008Awange et al, , 2014Hassan and Jin, 2004), satellite precipitation data for studying the lake's rainfall (e.g., Kizza et al, 2009;Awange et al, 2013b), a combination of both ground-based and remotely sensed observations for studying the lake's water balance (e.g., Yin and Nicholson, 1998;Swenson and Wahr, 2009). Despite this plethora of studies, a precise study of the hydrological processes of Lake Victoria using merged and improved coherent datasets from multiple sources, what would also benefit other inland lake waters the world over, is still missing.…”
Section: Introductionmentioning
confidence: 99%
“…To achieve higher spatial resolution with microwave systems requires active radar, which exploits the relationship between the radar backscatter coefficient and soil moisture (Oh et al, 1992). Non-imaging radar systems include scatterometers (Bartalis et al, 2007) and radar altimeters (Uebbing et al, 2017). Synthetic aperture radar (SAR) is an active microwave imaging technology with high spatial resolution (10-50m).…”
Section: Introductionmentioning
confidence: 99%